Sistem Deteksi Kebakaran Menggunakan Esp32 Dan Arduino - Muhammad Ainun Najib; Adam Syuhada; Wahyu Dika Irfianton; Sulartopo Sulartopo (Universitas Sains dan Teknologi Komputer, 2023)
,. Fire disasters are disasters that occur more often than other disasters such as floods, landslides, earthquakes or tsunamis. This disaster can happen at any time and no one knows for sure when this disaster will come. The impact of a fire disaster is not only material but can result in the loss of human life. Factors that cause fire disasters often occur due to human negligence and fires often occur in houses where the occupants are abandoned. The research carried out this time focuses on creating a fire detection system using ESP32 and Arduino. The system uses three sensors, namely a temperature sensor, a gas sensor and a fire sensor. Temperature sensors are useful for monitoring room temperature conditions, fire sensors are useful for detecting the presence of fire in a fire disaster and gas sensors are useful for detecting the presence of smoke that appears as a result of a fire disaster. This system uses Arduino Uno and ESP32 microcontrollers. The results of the fire detection system are expected to reduce the occurrence of fire accidents and also losses caused by fire accidents